Shaping the text, shaping the mind: role of transcultural imagination on the building of spiritual bridges of solidarity across boundaries of difference - Klímová, Zuzana, 1984-; Franková, Milada, 1946-; Masarykova univerzita. Katedra anglistiky a amerikanistiky (2016)
Záměrem této disertační práce je snaha o prozkoumání možností literatury na vývoj mezilidských vztahů v kontextu globální společnosti. Prvním úkolem bylo reagovat na současnou situaci v oboru postkoloniálních studií, které v současné době prožívají krizi spjatou zejména s pojmem postkolonialismu jako takového a jeho problematickou aplikací na současnou společnost. Dalším aspektem teoretického výzkumu této práce je snaha o nalezení sjednocujícího principu postkoloniálních studií v průběhu jejich vývoje, který charakterizují změny v přístupech a také cílích jednotlivých přístupů. Jedním ze závěrů je návrh na přijetí solidarity jako jednoho z možných prvků charakterizujících všechny jednotlivé přístupy v rámci postkoloniálních studií, který je zároveň dostatečně flexibilní, aby dokázal reagovat na změny ve společnosti a přesto zachoval nároky na použitelnost teoretického přístupu a také možnost jeho praktického využití, což odpovídá původním záměrům postkoloniálních studií o nápravu neeti
Aim of this dissertation is to analyse the potential of literature to influence the development of interpersonal relationships in the global context. The first task was to react to the contemporary situation in the field of Postcolonial Studies which are under a severe pressure because of the applicability of its central terminology and approaches. I have tried to identify the uniting principle of postcolonial discussions that might solve the problem of terminology and at the same time reflect current needs of the field. The concept of solidarity seems to be a suitable option which reflects the needs of Postcolonial Studies calling for the just and equal world while tackling the core questions of division of power between groups. Processes behind solidarity formation revolve around the problem of (self-)identification and differentiation and especially around the artificial ascription of value to individual groups based on the characteristics that are not qualitative. The practical pa
Vedoucí práce: Milada Franková
Dizertace (Ph.D.)--Masarykova univerzita, Filozofická fakulta, 2016
Keywords: postkoloniální literatury; solidarita; postcolonial literature; solidarity; disertace; dissertations